1997
DOI: 10.1007/bf02055684
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous butyrate and healing of colonic anastomoses in the rat

Abstract: We conclude that intravenous butyrate improves mechanical strength of a colonic anastomosis without a detectable change in total collagen content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
8

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 10 publications
0
20
1
8
Order By: Relevance
“…Desta forma, em situações de ausência de trânsi-to intestinal, tem sido orientada a suplementação de AGCC tanto por aplicação local direta, via retal, quanto por via endovenosa 13 , na tentativa de minimizar os efeitos atróficos normalmente observados.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Desta forma, em situações de ausência de trânsi-to intestinal, tem sido orientada a suplementação de AGCC tanto por aplicação local direta, via retal, quanto por via endovenosa 13 , na tentativa de minimizar os efeitos atróficos normalmente observados.…”
Section: Discussionunclassified
“…Em 1997, Rolandelli et al 13 avaliaram a ação do AGCC aplicado via endovenosa, e também não encontraram diferença no conteúdo de hidroxiprolina; mas observaram que a resistência mecânica era maior no grupo que havia recebido AGCC em comparação com o grupo controle.…”
Section: Greca Et Alunclassified
“…Da Costa et al 23 studied the effects of oral GLU supplementation on the healing of colonic anastomosis in rats and they also reported improvement in BP and increased mature collagen in the GLU group. Rolandelli et al 24 investigated the effects of butyrate infusion on the healing of colonic anastomosis in rats and the authors observed improvement of BP in the butyrate group. Williams et al 4 also reported that healthy elderly volunteers given a dietary supplementation of specialized amino acid mixture accumulated 67% more collagen, as assessed by the HP content and had significantly improved wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…While there seems to be a detrimental effect of osmotic agents used for bowel preparation on colonic tissue, a beneficial effect of butyrate has been reported. This short chain fatty acid is produced through bacterial fermentation in the large bowel and was reported to have a hypertrophic and healing-promoting effect on colonic tissue in animal and human studies [22][23][24][25][26][27][28][29]. Previous studies have shown a beneficial effect of continuous irrigation with this agent on the healing of colon anastomoses in rats [22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…This short chain fatty acid is produced through bacterial fermentation in the large bowel and was reported to have a hypertrophic and healing-promoting effect on colonic tissue in animal and human studies [22][23][24][25][26][27][28][29]. Previous studies have shown a beneficial effect of continuous irrigation with this agent on the healing of colon anastomoses in rats [22][23][24]. In our study, we analysed the effect of a single dose of intra-operatively administered butyrate on colonic anastomotic healing, as this would be the most feasible way of administration in human colon surgery.…”
Section: Introductionmentioning
confidence: 99%